Integration of Ultrasound into the Development of Plant-Based Protein Hydrolysate and Its Bio-Stimulatory Effect for Growth of Wheat Grain Seedlings In Vivo - Karolina Trakselyte-Rupsiene; Grazina Juodeikiene; Darius Cernauskas; Elena Bartkiene; Dovile Klupsaite; Daiva Zadeike; Joana Bendoraitiene; Jonas Damasius; Jonas Ignatavicius; Sidona Sikorskaite-Gudziuniene (Plants, 2021)
This study was dedicated to increasing the efficiency of producing plant-based protein hydrolysate using traditional and non-traditional treatments. Low- and high frequency ultrasound (US) at different intensities were applied to corn steep liquor (CSL) at 50 °C for 30 min, and enzymatic hydrolysis was performed using industrially produced alkaline protease. The efficiency of US and enzymatic treatments was characterized by protein solubility (soluble protein (SP) content, hydrolyzed protein (HP) concentration, and free amino acid (FAA) profile) and kinetic parameters: Michaelis–Menten constant (KM) and apparent breakdown rate constant (kA). A significant effect of 37 kHz US pre-treatment for CSL enzymatic hydrolysis was found and resulted in the highest HP concentration (17.5 g/L) using the lowest enzyme concentration (2.1 g/L) and the shortest hydrolysis time (60 min). By using US pre-treatment, on average, a 2.2 times higher FAA content could be achieved compared to traditional hydrolysis. Additionally, results for the kinetic parameters kM and kA confirmed the potential of applying US treatment before hydrolysis. The effect of CSL protein hydrolysate on plant growth was tested in vivo on wheat grain seed germination and resulted in the significant increase in germination parameters compared to the control treatment. These findings indicate that by-products of starch industry could be a promising source for the production of low-cost sustainable biostimulants.